APPLICATION OF RELIGIOUS VALUES IN THE FORMATION OF CHILDREN ISLAMIC CHARACTER IN THE KHADIJAH TEACHING HOME ON ROAD KELAMBIR LIMA - Br. Sitepu, Nopita Sari; Imran, Zulfi (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
Religious values are several social systems that regulate beliefs, behavior, social rules in carrying out the lives of fellow human beings, as well as ways of worshiping Allah SWT, this is also an effort in developing group and individual knowledge about the teachings that Allah has set in the Qur'an. 'an, and also all forms of provisions of life as well as regulations that must be accepted by humans as prohibitions, and orders, so that if these orders are violated then they will receive the punishment given by Allah in the hereafter. Character formation is basically a view of the relationship that every human being has, namely the relationship to oneself, to the environment, and to the creator, this becomes a value and belief in the growth of a child's attitude. Character building aims to instill certain attitudes in children so that they educate positive behaviors such as forming a sense of caring, responsibility, having a sense of justice, being persistent, diligent and having a sense of respect for others. The development of the child's character must start from learning his manners, morals, and religion. The lack of alertness from the role of parents creates a moral crisis that has negative consequences in society, for example, against children against their parents, promiscuity, theft, drug abuse and violence against people of their age or below.